1978
DOI: 10.1037/0003-066x.33.7.703
|View full text |Cite
|
Sign up to set email alerts
|

What happens to PhD program applicants who have master's degrees?

Abstract: Dawes, R. M. Formal models of dilemmas in social decision making. In M. F. Kaplan & S. Schwartz (Eds.), Human judgment and decision processes; Formal and mathematical approaches. New York: Academic Press, 1975. Dawes, R. M., McTavish, J., & Shaklee, H. Behavior, communication, and assumptions about other people's behavior in a commons dilemma situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

1979
1979
1985
1985

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…That is, if the undergraduate record is a good predictor of success in PhD programs, then it follows that the undergraduate record combined with the master's program record should be an even better predictor of success. In support of this reasoning, Annis et al (1978) noted that several PhD programs reported that applicants holding master's degrees were more likely to complete the PhD if accepted than were students entering with only the bachelor's.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…That is, if the undergraduate record is a good predictor of success in PhD programs, then it follows that the undergraduate record combined with the master's program record should be an even better predictor of success. In support of this reasoning, Annis et al (1978) noted that several PhD programs reported that applicants holding master's degrees were more likely to complete the PhD if accepted than were students entering with only the bachelor's.…”
mentioning
confidence: 98%
“…A recent survey by Annis, Tucker, and Baker (1978) indicated that PhD programs in clinical and counseling psychology, especially those approved by the American Psychological Association (APA), were less likely to accept applicants who held degrees from terminal master's programs than those who held only bachelor's degrees. However, Annis et al also found that terminal master's degree holders were viewed as equal to or more qualified than bachelor's-only applicants by nearly all (97%) of the department chairpersons surveyed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely recognized that gaining admission to a PhD program in clinical psychology is difficult. Indeed, some people have described this process as "fierce" (Annis, Tucker, & Baker, 1978). It is equally widely recognized that the Graduate Record Examination (GRE) is one of the heaviest weighted of all admissions variables.…”
mentioning
confidence: 99%
“…It is difficult to gain admission to many PhD and PsyD programs, and a master's degree may be the only choice for some qualified individuals (or the degree of choice for others). One can earn a master's degree and apply to doctoral programs with hopes of admission (Annis, Tucker, & Baker, 1978;Mealiea, 1973;Perlman, in press;Tucker & Annis, 1981). Korn (1984) recently estimated that the odds on gaining doctoral program acceptance seem to be improving (although he did not look at master's-level individuals per se) while LeUnes, Bourgeois, Bond, and Oppenheimer (1982) argue for in-depth follow-up of master's programs.…”
mentioning
confidence: 97%